Effect of Aging on the Properties of Asphalt and Asphalt Mixtures - Higuera Sandoval, Carlos Hernando (2015)
This article presents the results of the analysis of the effect of aging on the properties of asphalt and asphalt mixtures. The objective of this study was to compare the properties of the original asphalt and aged asphalt and the dynamic modulus of asphalt mixtures. The long-term aging was simulated by using Pressure Asphalt Vessel (PAV). Marshall and RAMCODES methodologies were used to determine the formula of work; values of dynamic modulus of designed mixtures were obtained by the indirect tensile test, using the Nottingham Asphalt Tester (NAT). The results showed an increase in the rigidity of the aged asphalt. Also, an increase of the stability and a decreased flow in the mixtures made with this type of binder was found. The dynamic modulus values of the mixtures containing aged asphalt showed an increase up to three times compared with those elaborated with original asphalt mixtures.